2018
DOI: 10.1007/s00253-018-8992-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenomic screening approach to identify new antigens for the serological diagnosis of chronic Chagas’ disease

Abstract: Serological tests are preferentially used for the diagnosis of Chagas' disease (CD) during the chronic phase because of the low parasitemia and high anti-Trypanosoma cruzi antibody titers. However, the current methods showed several disadvantages, as contradictory or inconclusive results, mainly related to the characteristics of the antigens used, in general, crude or whole parasites, but also due to antigen production protocol and the experimental conditions used in serological tests. Thus, better-quality ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Here, Chagas-specific motifs mapped to distinct candidate antigens. Several of these antigens have been reported 25 , while others have not been described previously. Approaches to antigen discovery from biospecimens often require laborious antigen cloning, expression, purification, and reactivity testing 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Here, Chagas-specific motifs mapped to distinct candidate antigens. Several of these antigens have been reported 25 , while others have not been described previously. Approaches to antigen discovery from biospecimens often require laborious antigen cloning, expression, purification, and reactivity testing 26 .…”
Section: Discussionmentioning
confidence: 98%
“…In order to solve the problems of sensitivity and/or specificity, as described above, studies has been carried out to identify new antigens candidates based on experimental approaches evaluating in silico prediction data by immunoinformatics and published genomes [27, 45]. This strategy allows the rational search for antigenic proteins, as well as to determine the regions of these targets that determine the antigenicity and specificity for the recognition of the targets by sera from patients [27, 48].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, evaluating peptides ELISA assays, high sensitivity values were observed, that ranging from 82.86–100.00%, included peptide mixtures (Mix I, II, III and IV), and can be explained by high expression in intracellular stages, subcellular localization (secreted/excreted) and high antigenicity demonstrated by B-cell prediction. In according, previous studies have demonstrated that proteins expressed in stages found in vertebrate host are possibly associated with with the infection process and/or the intracellular survival of the parasite within the host, and may be attractive diagnostic targets [30, 45, 49]. Serological tests have also presented limitations regarding the absence of correlation between the antibody levels and the current stage of the disease [21, 50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations